Use of the Canva Application in Islamic Religious Education Learning for Grade XI Students of State Vocational School in Indonesia - Efendi, Yusuf; Chaniago, Fransisko (POTENSIA: Jurnal Kependidikan Islam, 2026)
This research was motivated by the low interest and learning outcomes of students in Islamic Religious Education at SMK Negeri 8 Sarolangun, caused by the use of monotonous conventional lecture methods, particularly for complex marriage top-ics. The purpose of this study was to describe the integration of the Canva applica-tion in Islamic Religious Education learning, identify supporting and inhibiting fac-tors, and analyze its impact on the learning process of 11th-grade Accounting stu-dents. This study used a descriptive qualitative approach, collecting data through observation, documentation, and in-depth interviews with the Islamic Religious Education teacher and 11th-grade Accounting students. The results showed that the use of Canva was able to transform abstract marriage material into interactive and systematic visualizations. The main supporting factor was the accessibility of Canva's user-friendly features, while the main obstacle lay in the unstable internet connection at the school. The implementation of this media was proven effective in increasing student learning motivation and cognitive outcomes, as students be-came more active in constructing their understanding through creative design. In conclusion, the use of the Canva application is an effective pedagogical innovation in synergizing digital technology with religious material to create more dynamic and meaningful learning.